2016
DOI: 10.1377/hlthaff.2015.0965
|View full text |Cite
|
Sign up to set email alerts
|

Workers Without Paid Sick Leave Less Likely To Take Time Off For Illness Or Injury Compared To Those With Paid Sick Leave

Abstract: Paid sick leave is an important employer-provided benefit that helps people obtain health care for themselves and their dependents. But paid sick leave is not universally available to US workers. Little is known about paid sick leave and its relationship to health behaviors. Contrary to public health goals to reduce the spread of illness, our findings indicate that in 2013 both full- and part-time working adults without paid sick leave were more likely than workers with that benefit to attend work when ill. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 11 publications
3
104
0
3
Order By: Relevance
“…The data bears out the important role paid sick leave plays in reducing the likelihood of employees going to work when they're sick (DeRigne et al, 2016;Piper et al, 2017;Schneider, 2020). Studies have found that workers who lack paid sick leave are 1.5 times more likely to go to work contagious (Smith & Kim, 2010) and less likely to see a health care provider when sick (Cordoba & Aiello, 2016).…”
Section: Paid Sick Leave When the Economy Is Openmentioning
confidence: 97%
“…The data bears out the important role paid sick leave plays in reducing the likelihood of employees going to work when they're sick (DeRigne et al, 2016;Piper et al, 2017;Schneider, 2020). Studies have found that workers who lack paid sick leave are 1.5 times more likely to go to work contagious (Smith & Kim, 2010) and less likely to see a health care provider when sick (Cordoba & Aiello, 2016).…”
Section: Paid Sick Leave When the Economy Is Openmentioning
confidence: 97%
“…4,5 Thus, having PSL has been associated with decreased nosocomial respiratory and gastrointestinal disease outbreaks. 6 Despite this association, 39% of civilian employees in the U.S. do not receive PSL.…”
Section: Introductionmentioning
confidence: 99%
“…Lower-wage, part-time and service sector workers are less likely than average to have paid leave [2]. Access to paid sick leave is associated with using preventative care including routine cancer screenings, [3, 4] parents’ ability to take care of sick children, [5, 6] and worker willingness and financial ability to avoid the workplace when ill [7, 8]. Expanding sick leave may reduce the spread of infectious diseases including influenza [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of job protections and paid time off might limit use of new health coverage among workers hoping to avoid financial penalty for missed work. Hence for low-income populations, access to paid leave might increase the use of ACA-mandated health benefits [8]. …”
Section: Introductionmentioning
confidence: 99%